Vyavasthapan aani utpadan niyojan (TYBCom) - Liman M.S., Rawerkar Deepak, Wadekar P.M., Gonda M.G. etc. (Sheth Pub., Mumbai, 2005)
Commerce
MARATHI
Keywords: Vyavasthapan aani utpadan niyojan (TYBCom); Commerce; Commerce